Representing the post-apartheid township and the rural: the case of ETV’s Ekasi: Our Stories, Mzansi Magic’s Lokshin Bioskop and Mzansi Movies - Selekane, Nkosinathi Leonard (My University, 2020)
In this study, through the reading of selected popular films commissioned by ETV through Ekasi: Our Stories and Mzansi Magic via Lokshin Bioskop and Mzansi Movies, I investigate the narratives and aesthetics that are embedded in the films that are aligned to post-apartheid nation-building and neoliberal archetypes. In an attempt to address the above hypothesis, I examine how narratives and aesthetics of neoliberalism and nation-building buttress the concealing of realities about black spaces. The central argument emanating from this study is that the popular films by South African private television networks seem to significantly represent a sugarcoated view of blackness, the township and rural spaces, in the ploy to lionize the post-1994 democratic dispensation. Popular arts in Africa by Karin Barber (1987, 1997, 2000), alongside Critical Political Economy of the Media (CPEM) and Third Cinema are applied in the task to extrapolate the representations portrayed by the selected films that have been commissioned by private television networks. The films in this study draw from popular discourses that exist in contemporary creolised culture to construct nation-building, aspirational and neoliberal narratives (Hannerz, 1987; Mhlambi, 2012). The findings divulge a return of apartheid representations that were created by filmmakers who were co-opted by the state into creating content that worked to neutralise black ambitions for liberation and political consciousness. Also, narratives that promote black middle-classness together with conspicuous consumption are advanced to create a perception about the township as progressive. In support of nation-building and neoliberal ideals, some narratives of poor spaces present tropes that shift the blame for the plight of the underclass away from the state towards individual failures to deploy mechanisms of self -help. Foreign nationals are presented as a scapegoat for the failures of the government to improve the lives of township dwellers. Multicultural and multilingual narratives are presented by the films in the exertion to advance nation-building that is veered towards solidifying Black Nationalism that this current dispensation is based on. This is done at the expense of the gender project. In the representation of the rural spaces, the films confront issues of patriarchy in the ploy to advance the status of rural spaces as progressive black living spaces and in so doing, the themes of the ‘Back to the Homelands’ films are brought into this present epoch. Alarmingly, the television networks that commissioned the films in this study are private broadcasters that are hypothetically perceived as not vulnerable to manipulation by government, as is the case with public broadcasters. Tropes that were deployed by apartheid popular film and television seem to reemerge in productions by private television entities to cement the present political economy
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the Degree of Doctor of Philosophy